Analysis of immortal-time effect in post-infarction ventricular septal defect - González-Pacheco, Héctor; Ortega-Hernandez, Jorge Arturo; Meza-López, Jesús Ángel; Soliz-Uriona, Luis Alejandro; Manzur-Sandoval, Daniel; Gopar-Nieto, Rodrigo; Araiza-Garaygordobil, Diego; Sierra-Lara, Daniel; Arias-Sánchez, Eduardo; Sandoval, Juan Pablo; Altamirano-Castillo, Alfredo; Mendoza-García, Salvador; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Time-fixed analyses have traditionally been utilized to examine outcomes in post-infarction ventricular septal defect (VSD). The aims of this study were to: (1) analyze the relationship between VSD closure/non-closure and mortality; (2) assess the presence of immortal-time bias. Material and methods In this retrospective cohort study, patients with ST-elevation myocardial infarction (STEMI) complicated by VSD. Time-fixed and time-dependent Cox regression methodologies were employed. Results The study included 80 patients: surgical closure (n = 26), transcatheter closure (n = 20), or conservative management alone (n = 34). At presentation, patients without VSD closure exhibited high-risk clinical characteristics, had the shortest median time intervals from STEMI onset to VSD development (4.0, 4.0, and 2.0 days, respectively; P = 0.03) and from STEMI symptom onset to hospital arrival (6.0, 5.0, and 0.8 days, respectively; P < 0.0001). The median time from STEMI onset to closure was 22.0 days (P = 0.14). In-hospital mortality rate was higher among patients who did not undergo defect closure (50%, 35%, and 88.2%, respectively; P < 0.0001). Closure of the defect using a fixed-time method was associated with lower in-hospital mortality (HR = 0.13, 95% CI 0.05–0.31, P < 0.0001, and HR 0.13, 95% CI 0.04–0.36, P < 0.0001, for surgery and transcatheter closure, respectively). However, when employing a time-varying method, this association was not observed (HR = 0.95, 95% CI 0.45–1.98, P = 0.90, and HR 0.88, 95% CI 0.41–1.87, P = 0.74, for surgery and transcatheter closure, respectively). These findings suggest the presence of an immortal-time bias. Conclusions This study highlights that using a fixed-time analytic approach in post-infarction VSD can result in immortal-time bias. Researchers should consider employing time-dependent methodologies.